Russia's energy problem. Issue 8 (14th September 2022) - Unknown
Abstract : Global energy markets have experienced shocks from the coronavirus pandemic and Russia's war in Ukraine. Moscow may have thought, upon launching the war, that its energy exports would be a strength that would both restrain Europe's reaction and serve as a financial lifeline to the rest of the world in the face of economic sanctions imposed by the West. This gamble did not pay off, however, partly because of the pace of change taking place in energy markets. Indeed, it now looks as if energy exports may no longer serve as an engine of growth and vitality for the Russian economy.